ANALYSIS OF THE PERCEPTION OF MOBILE FOOD TRADERS REGARDING ULTRA-MICRO BUSINESS FINANCING POLICIES IN THE ERA OF THE COVID 19 PANDEMIC IN THE CITY OF MEDAN - Hastina Febriaty; Julianda Leli Monika (Proceeding International Seminar of Islamic Studies, 2022)
The role of micro, small and medium enterprises is very important to drive the economy both nationally and regionally. such as moneylenders. In fact, this is actually a problem for small business actors, because of high interest rates, heavy installments, and the consequences of heavy delays in installments. This research was conducted in several street vendors in the city of Medan. The reason for choosing this area is because it is one of the metropolitan cities with ultra-micro businesses that are spread evenly around the city of Medan.The result of this research is that the ultra micro business financing provided by Mekaar or Pegadaian has a major effect on changes in selling capital, changes in income and changes in business development before and after sales capital for ultra micro businesses in Medan City. This is evidenced by the increase in sales capital after receiving financing.And the government's effort to overcome this is by establishing PT.PNM Mekaar as a realization the government's real commitment to develop, promote and maintain micro, small and medium enterprisesKeywords: Mobile food traders, Micro business financing for ultra micro businesses.